1972
DOI: 10.1002/tea.3660090315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subsuming concepts on student achievement on unfamiliar science learning material

Abstract: Students enrolled in an undergraduate chemistry class were rank ordered by their performance on a test of organizing ability. The median break was used to form two groups: good organizers (GO) and poor organizers (PO). Students within these groups were randomly assigned to treatments. Treatment I subjects received an advance organizer followed by a learning passage. Treatment II subjects received the same organizer preceeded by the learning passage. Treatment in subjects received an historical nonorganizer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Results supporting the superiority of the advance organizer group have been reported for target passages concerning a wide range of topics (Allen, 1969;Anderson, 1973;Ausubel & Fitzgerald, 1961;Fitzgerald & Ausubel, 1963;Grotelueschen & Sjogren, 1968). However, a number of investigators using very similar paradigms have found no difference between groups (Clawson & Barnes, 1973;Graber, Means, & Johnsten, 1972;Jerrolds, 1967). The nature of the interaction of individual intellectual ability and organizer effects is similarly unclear.…”
Section: Methodsmentioning
confidence: 99%
“…Results supporting the superiority of the advance organizer group have been reported for target passages concerning a wide range of topics (Allen, 1969;Anderson, 1973;Ausubel & Fitzgerald, 1961;Fitzgerald & Ausubel, 1963;Grotelueschen & Sjogren, 1968). However, a number of investigators using very similar paradigms have found no difference between groups (Clawson & Barnes, 1973;Graber, Means, & Johnsten, 1972;Jerrolds, 1967). The nature of the interaction of individual intellectual ability and organizer effects is similarly unclear.…”
Section: Methodsmentioning
confidence: 99%
“…Another problem with this study is that in-class interaction during the study could have provided the needed subsuming ideas and thus washed out the effects of organizers. Graber et al (1972) also failed to report means so that it is not possible to make a comparison of raw scores for the AO and PO groups. However, these authors point out that this replication of Ausubel's (1960) original study may have failed to produce significant results because Ausubel used subjects who were No means (Note: Organizers not really subsumers) Bertou et al (1972), 176 9th graders 1.…”
Section: Modified Advance Organizer Studiesmentioning
confidence: 99%
“…Negative findings concerning the usefulness of advance organizers have also been reported (e.g., Graber, Means, & Johnston, 1972). This is not * particularly surprising given the canplexity of the relation between schemata which are essentially as novel to the subject at the time of their presentation as the target material itself.…”
Section: Schemata and Transfermentioning
confidence: 95%